The rag Locus of Porphyromonas gingivalis Contributes to Virulence in a Murine Model of Soft Tissue Destruction - Shi, Xiaoju (American Society for Microbiology, 2007)
The rag locus of Porphyromonas gingivalis encodes a putative TonB-dependent outer membrane receptor, RagA, and a 55-kDa immunodominant antigen, RagB. Inactivation of either ragA or ragB prevented expression of both RagA and RagB. Both the ragA and ragB mutants were significantly less virulent than wild-type strains in a murine model of infection.